2018
DOI: 10.1108/rmj-08-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Ethnographic sensitivity and current recordkeeping

Abstract: Purpose The purpose of this paper is to report on the application of information culture analysis techniques in the workplace. The paper suggests that records managers should use ethnographic sensitivity, if they want to have a constructive dialogue with records creators and users, and effect positive change in their organisations. Design/methodology/approach Two pilot studies were conducted in university settings for the purpose of testing an information culture assessment toolkit. The university records ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The information culture of an organisation is influenced by many factors, including the national and regional culture, the organisation type, its purpose and its history, its organisational structure, the personality of its leaders and the background and skills of its employees (Oliver, 2008;Choo et al, 2008;Lian et al, 2022). Oliver and Foscarini (2020) developed a 3-level Information Culture Framework to analyse the information culture of organisations, which identifies the factors that are easy to change in order to improve information practices in an organisation, the factors that are harder to change, and the factors that are very difficult to change because they are based on deep-seated cultural preferences or on external elements. The latter, the Level 1 factors, include the preferences for information formats (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The information culture of an organisation is influenced by many factors, including the national and regional culture, the organisation type, its purpose and its history, its organisational structure, the personality of its leaders and the background and skills of its employees (Oliver, 2008;Choo et al, 2008;Lian et al, 2022). Oliver and Foscarini (2020) developed a 3-level Information Culture Framework to analyse the information culture of organisations, which identifies the factors that are easy to change in order to improve information practices in an organisation, the factors that are harder to change, and the factors that are very difficult to change because they are based on deep-seated cultural preferences or on external elements. The latter, the Level 1 factors, include the preferences for information formats (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas most of the recordkeeping literature has been concerned with assessing whether organisations were correctly managing records in accordance with legislation and best practice standards and with finding ways of improving recordkeeping practices in organisations so that they comply with laws and standards, a growing strand of research argues that to be effective and sustainable, recordkeeping practices must be adapted to the information culture of the organisations (Oliver and Foscarini, 2020; Oliver et al, 2018; Lian et al, 2022; Frings‐Hessami & Oliver, 2022a, 2022b). Recordkeeping in an organisation is impacted by the information culture of the organisation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a business in Canada is going to have a very different information culture than one in South Korea. Oliver et al (2018) take this one step further by linking information culture to the practice of what they describe as scaled down "ethnography-lite", (the scientific study of peoples and their cultures). Their article, which uses 2016 version of the Information Culture(s) Toolkit published by the International Council on Archives (Oliver et al, 2019) as a framework, found that if people do not understand why recordkeeping is important, then there is "a disconnect between recordkeeping compliance approaches and expectations, on the one hand, and the practices and preferences of the staff, on the other" (p. 179).…”
Section: Information Culturementioning
confidence: 99%
“…But, although this efficiency could be credited to a records manager ensuring rigid compliance, case studies have found that effective records managers are flexible and cooperative. Oliver and Foscarini (2020) are some of the leaders in this more humanistic approach, saying that:…”
Section: Evolution Of Records Managementmentioning
confidence: 99%
See 1 more Smart Citation